Peningkatan Keterampilan Membaca Melalui Penerapan Metode Survey Question Reading Recite Review Pada Siswa Kelas V Sd Negeri 2 Gedongjetis Tahun 2014/2015 - Kuncara, Muhamad Sigit Adi, Dr. Achmad Fathoni, M.Pd (2017)
The purpose of this research is to improve the ability to read in class V students of Primary STATE 2 Gedongjetis years 2014/2015. This research is a classroom action research. The subjects of this study were 17 students of class V Primary School 2 Gedongjetis. This research in the form of collaboration or cooperation between researchers with the class teacher V. This study comprises two (2) cycles, each cycle consisting of four phases, namely planning, action, observation, and reflection. Data collection techniques used were observation, test, and document. To test the validity of the data the author uses the validity of the instrument and the validity of the data in it using triangulation. Data analysis technique used is data reduction, data presentation, and conclusion. This research is a classroom action research. The subjects of this study were 17 students of class V primary school 2 Gedongjetis. This research in the form of collaboration or cooperation between researchers with the class teacher V. This study comprises two (2) cycles, each cycle consisting of four phases, namely planning, action, observation, and reflection. Data collection techniques used were observation, test, and document. To test the validity of the data the author uses the validity of the instrument and the validity of the data in it using triangulation. Data analysis technique used is data reduction, data presentation, and conclusion. The results of the study before implementation cycles result that amounted to 41.17% (7 students) scored ≥70 (KKM) of 17 students. In the implementation of the first cycle of learning outcomes of students increased to 70.58% (12 students) scored ≥ 70 (KKM) of 17 students. On the implementation of the second cycle learning outcomes of students increased by 17.65% from the first cycle to 88.23% (15 students) scored ≥ 70 (KKM) of 17 students. Based on these studies it can be concluded that the application of strategi survey question Recite reading the reviews can improve students' reading ability in Indonesian Language class V Primary School Klaten Gedongjetis years 2014/1015.